2010
DOI: 10.1007/s00280-010-1537-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a non cystatin-C-based novel algorithm to calculate individual glomerular filtration rate in cancer patients receiving carboplatin

Abstract: These results suggest that the concept of a non cystatin C-based novel algorithm including three different formulas rather than one single equation may improve accurate estimation of GFR over a broad range of constitutive values, including patients with low constitutive renal function as well as overweight patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the 8 studies that reported mCL Cr, the mean was 81AE21 mL/ min. 15,19,20,22,23,31,32 No studies reported measured GFR. The Cockcroft-Gault formula was the primary serum creatinineebased reference equation studied, and several approaches to estimating GFR from cystatin C (eGFR Cystatin C ) were reported, including the CKD EPI, Flodin, Larsson, Hoek, Macdonald, and Sjostrom equations.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
“…In the 8 studies that reported mCL Cr, the mean was 81AE21 mL/ min. 15,19,20,22,23,31,32 No studies reported measured GFR. The Cockcroft-Gault formula was the primary serum creatinineebased reference equation studied, and several approaches to estimating GFR from cystatin C (eGFR Cystatin C ) were reported, including the CKD EPI, Flodin, Larsson, Hoek, Macdonald, and Sjostrom equations.…”
Section: Study Identification and Characteristicsmentioning
confidence: 99%
“…The data for the use of serum cystatin C to estimate GFR in patients with stable renal function and consequently drug clearance are somewhat limited but promising. Several renally eliminated medications have been tested including antimicrobial agents, cardiovascular drugs, and chemotherapeutics, but strategies to implement the use of this biomarker routinely at the bedside are lacking . In the case of vancomycin, serum cystatin C or the associated eGFR better predicted vancomycin clearance than creatinine in pharmacokinetic models, especially among those with altered skeletal muscle mass …”
Section: Practical Models Of Biomarker Utilizationmentioning
confidence: 99%
“…Several renally eliminated medications have been tested including antimicrobial agents, cardiovascular drugs, and chemotherapeutics, but strategies to implement the use of this biomarker routinely at the bedside are lacking. [22][23][24][25][26][27][28][29] In the case of vancomycin, serum cystatin C or the associated eGFR better predicted vancomycin clearance than creatinine in pharmacokinetic models, especially among those with altered skeletal muscle mass. [30][31][32][33][34][35] Case Study: Cystatin C for Vancomycin Dosing…”
Section: Practical Models Of Biomarker Utilizationmentioning
confidence: 99%
“…Holweger et al [1] calculated carboplatin administered dose by a modified Calvert formula whereas GFR was substituted by CrCl via 24-h urine collection or calculated by Jelliffe. We don't know how many patients were dosed with 24-h urine collection or with Jelliffe formula in this study.…”
Section: Estimating the Correct Way Of Calculating The Carboplatin Dosementioning
confidence: 99%
“…In this study, that included 290 patients, the best method to estimate GRF was Cockcroft-Gault. In Holweger et al study [1] the Cockcroft-Gault estimation in obese patients was carried out using the actual body weight. It is known that when actual body weight is used, in patients with BMI>30kg/m 2 , it can conduce to overdosification.…”
Section: Estimating the Correct Way Of Calculating The Carboplatin Dosementioning
confidence: 99%